Piperonyl butoxide (PBO) combined with pyrethroids in long‐lasting insecticidal nets (LLINs) to prevent malaria in Africa - Gleave, Katherine (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: 1. Evaluate whether adding PBO to pyrethroid LLINs increases the epidemiological and entomological effectiveness of the nets. 2. Compare the effects of PBO‐LLINs currently in commercial development or on the market with their non‐PBO equivalent in relation to: a. malaria infection (prevalence or incidence); b. entomological outcomes.